The role of Th-U minerals in assessing the performance of nuclear waste forms. (October 2014) - Lumpkin, G. R.; Gao, Yan; Gieré, R.; Williams, C. T.; Mariano, A. N.; Geisler, T.
Abstract: Materials designed for nuclear waste disposal include a range of ceramics, glass ceramics and glass waste forms. Those with crystalline phases have provided the momentum for studies of minerals as a means to understand aspects of waste-form crystal chemistry, behaviour in aqueous systems and radiation damage over geological periods of time. Although the utility of natural analogue studies varies, depending upon the degree of analogy to the proposed geological repository and other factors such as chemical composition, the available data suggest that Th-U host phases such as brannerite, monazite, pyrochlore, zircon and zirconolite are resistant generally to dissolution in aqueous fluids at low temperatures. Geochemical durability may or may not extend to hydrothermal systems depending on the specifics of fluid composition, temperature and pressure. At elevated temperatures, for example, davidite may break down to new phase assemblages including titanite, ilmenite and rutile. Perovskite is generally less resistant to dissolution at low temperatures and breaks down to TiO2, releasing A -site cations to the aqueous fluid. Studies of radiation damage indicate that the oxide and silicate phases become amorphous as a result of the gradual accumulation of alpha-recoil collision cascades. Monazite tends to remain crystalline on geological time scales, a very attractive property that potentially eliminates major changes in physical properties such as density and volume, thereby reducing the potential for cracking, which is a major concern for zircon. In spite of recent success in describing the behaviour of Th-U minerals in geological systems, considerable work remains in order to understand the P-T-X conditions during alteration and T-t history of the host rocks.